Asian tourism demand for Malaysia : a bound test approach. - Mohd Salleh, Norlida Hanim; Law, Siong Hook; Ramachandran, Sridar; Shuib, Ahmad; Mohd Noor, Zaleha (2008)
The objective of this paper is to investigate the long-run and short-run relationships among tourist arrivals to Malaysia and tourism price, substitute price, traveling cost, income and exchange rate for Asian7. Theautoregressive distributed lag (ARDL) bounds test approach developed by Pesaran et al. (2001) is employed in the analysis, and the data cover the period 1970 to 2004. The empirical results show that in the long-run and short-run the tourism price, traveling cost, substitute price and income are the major determinants of Malaysia's tourism demand. The results also show that word-of mouth effect, world economic crisis (1997-98) and the outbreak of SARS (2002-03) significantly affected the demand for Malaysia's tourism in the short run. The findings are consistent with the economic theory and the model passed all the diagnostic tests.